Synergistic control of hand position, velocity, and acceleration fluctuates across time during simulated Nordic skiing - Frayne, D. H.; Norman-Gerum, V. T.; Howarth, S. J.; Brown, S. H. M. (Human Movement Science, 2022)
A central application of Uncontrolled Manifold (UCM) analysis is the quantification of the presence of motor synergies for the control of task-level variables during human movement. Choosing which task-level variable to analyse is a critical step in UCM analyses because this choice determines a relationship linking the motor performance and motor control. End-effector and/or centre of mass position are frequently chosen as task-level variables, whereas velocity and acceleration receive relatively little attention in this regard. Additionally, UCM analyses are most often conducted on discrete time points of a movement cycle, although these singular time points do not necessarily represent the characteristics of the whole cycle. Accordingly, the purpose of this investigation was to explore synergistic hand control during simulated Nordic skiing. It was hypothesized that 1) hand velocity would be a controlled task-level variable, 2) hand position would not be a controlled task-level variable, and 3) synergistic control of hand kinematics would be fluid (not constant throughout the movement cycle). Seven varsity-level skiers completed a simulated Nordic skiing task, producing specified power outputs on a Nordic skiing ergometer. Normalized time series of indices of task control from UCM analyses were analyzed using statistical parametric mapping. Synergies were observed for all of position, velocity, and acceleration (p < 0.0001), but not for the entire- skiing cycle. Therefore, UCM analyses conducted on discrete time points are not recommended without suitable a priori justification because its outputs fluctuate across time- especially during continuous movements. Velocity and acceleration should be considered in the choice of task-level variables, especially if they help define task performance.